Dukungan Keluarga Bagi Remaja dalam Menghadapi Pubertas di SMP Negeri 1 Kota Bima - Moh Ali (Bima Nursing Journal, 2020)
The family as the main social unit that gives influence to the growth and development of adolescents, the family is a place for individuals to learn to socialize, the success of adolescent development is achieved through interaction with family members. Optimal adolescent development will be achieved if they are with their families. Various factors can affect the development of adolescents, one of which is support from family members. This study aims to determine the relationship between perceptions of family social support with adolescent attitudes in dealing with puberty. This research is a correlational quantitative study with cross sectional approach, data were collected using a questionnaire, respondents were taken by simple random sampling technique in grade 1 and grade 2 students in SMP Negeri 1 Kota Bima, amounting to 76 respondents. There is a correlation between perceptions of family social support with adolescent attitudes in dealing with puberty analyzed with X2 = 39,269 and p-value: 0,000. Family social support greatly influences adolescent attitudes in dealing with puberty, forms of social support can be either material or non-material support.